2019
DOI: 10.7759/cureus.6061
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Early Morbidities in Low Birth Weight Neonates at The Aga Khan University Hospital, Karachi

Abstract: BackgroundGlobally, approximately 14.6% children are born with low birth weight (LBW) annually. In Pakistan, this figure however reaches approximately 16%. Low birth weight infants are vulnerable to develop early morbidities like hypothermia, hypoglycemia, respiratory distress syndrome and hypocalcemia. There is a scarcity of statistics which creates a gap in development of strategies for improving quality of care in developing countries. The aim of our study was to determine the frequency of early morbidities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 12 publications
1
2
1
Order By: Relevance
“…The predominant neonatal morbidities we observed were hypoglycaemia, hypocalcaemia and hyperthermia, which were significantly related to neonatal low birth weight. These findings are consistent with a study by Chand et al 26 .…”
Section: Discussionsupporting
confidence: 94%
“…The predominant neonatal morbidities we observed were hypoglycaemia, hypocalcaemia and hyperthermia, which were significantly related to neonatal low birth weight. These findings are consistent with a study by Chand et al 26 .…”
Section: Discussionsupporting
confidence: 94%
“…This finding was aligned with studies conducted in Thailand (44.15%),37 and Ethiopia 49.8 3%,38 The possible justification is due to similarities in study design, sample size and the presence of similar maternal health problems. On the other hand, this study was higher than two different studies conducted in Pakistan 11%–12.8%,15 16 India 38%,39 Nepal 21.4%40 and Nigeria 10.9% 19. The possible reason for this discrepancy is due to exclusion criteria.…”
Section: Discussioncontrasting
confidence: 69%
“…The magnitude of RDS among LBW neonates varies across countries depending on the availability of medical services and the number of trained medical personnel. For instance, in Taiwan 60%–86%,11 12 Finland 76%,13 Thailand 70.7%,14 Karachi, Pakistan 11%–12.8%,15 16 Iran 76%,17 Afghanistan 58.8%18 and in Nigeria 10.9%19 of LBW neonates had RDS. In Ethiopia, RDS is the primary cause of admission with a mortality rate of 45.3% among LBW neonates 20.…”
Section: Introductionmentioning
confidence: 99%
“…Another study by Chand et al [13] studied the early morbidities of LBW neonates, and found a significant association of birth weight with hypothermia and hypocalcemia, whereas gestational age was associated with hypocalcemia and respiratory distress syndrome. They also concluded that the priority should be given to adequate attention to LBW neonates.…”
Section: Online Firstmentioning
confidence: 99%